STRUKTUR DAN DIKSI TEKS LAPORAN HASIL OBSERVASI KARYA SISWA KELAS VII SMP NEGERI 24 PADANG - Novita, Yossy Sri; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT                 This study aims to (1) describe the structure of the report text of the observations of the work of class VII students of SMP Negeri 24 PAdang. (2) describe the diction of the report text of the observations by the VII grade students of SMP Negeri 24 Padang. The results of this study are (1) in writing the text of the report on the observation of the seventh grade students of Padang Public Middle School 24 using the three text structures of the observation report. The third structure of the report's text structure is the general definition, part description and description of benefits. This is evident from the 30 text reports on the results of the observations that have been analyzed, there are 28 complete observation report texts using general definitions, part descriptions, and description of benefits. (2) when viewed from diction usage with 94% accuracy of diction usage and 6% inaccurate use of diction in observation report text by class VII students of Padang Middle School 24. Kata Kunci: stuktur teks, diksi, dan teks laporan hasil observasi